Lipophilic antioxidant activity of guava fruit varieties palmira ica i, regional roja and regional blanca in four ripening stages (2012)
We determined the lipophilic antioxidant activity and β-carotene content with HPLC-UV in guava fruit Psidium guajava L.) varieties Palmira ICA I, Regional Roja and Regional Blanca in the ripening stages: green, semi-ripe, mature and senescent. It was established that the β-carotene content and lipophilic antioxidant activity increased during the ripening process up to the climacteric maximum and decreased during senescence; lipophilic antioxidant activity being higher in the varieties Palmira ICA I (13.06 μmol a-tocopherol/g fruit) and regional roja (14.08 μmol a-tocopherol/g fruit) and lower in the regional blanca variety (7.04 μmol a-tocopherol/g fruit), while β-carotene content was highest in the regional roja variety (85.26 Eq. retinol/100 g fruit) followed by the varieties Palmira ICA I (10.53 Eq. retinol/100 g fruit) and regional blanca (5.78 Eq. retinol/100 g fruit). The best correlation between lipophilic antioxidant activity and β-carotene content was observed in the ‘regional roja’ (r2 = 0.830), while the varieties Palmira ICA I and regional blanca showed no correlation.